Media education in the core curriculum of basic education in Portugal - Matos, A.P.M.; Bobrowicz-Campos, E.; Festas, I. (ICCL 2021 Proceedings – Livro de Atas e Livro de Resumos, 2021)
Over recent years, Portuguese compulsory education has undergone significant restructuring. The proposed changes covered, among others, the core curriculum of basic and secondary schools, complying with the recommendations for quality education, established by internationally acknowledged entities, including UNESCO [1] and OECD [2]. The present study, developed within the context of the COMEDIG project (PTDC/CED-EDG/32560/2017), aimed to map the presence of media-related content in the new core curriculum, taking into account all compulsory disciplines of basic education, from the first to the ninth grade. For this purpose, the qualitative analysis of 68 documents provided by the Directorate-General for Education and describing common reference base for learning was undertaken. The analysis considered the dimensions of media use, understanding and evaluation of media content or message, and production and communication of media content to others. Indications for using the media as an educational resource in the teaching and learning processes were integrated into the curricula of all years of basic education. As for the media literacy abilities, contents promoting their improvement were identified in several disciplines from the first to the ninth grade. However, the integrative three-dimensional approach, which simultaneously addresses accesses and uses, critical reflection, and production and communication, proved to be quite uncommon. Moreover, the referred contents focused predominantly on information and communication technologies and digital environments. There is a need to reinforce the presence of media education-related contents in the core curriculum of basic education in Portugal, proposing more integrative approaches and considering all media and in different supports.